On some variations of dominating identification in graphs: DOI: 10.48129/kjs.13175 - Fazil, Muhammad; Hussain, Iffat; Akbar, Ateqa; Ali, Usman (Kuwait Journal of Science, 2022)
A locating-dominating set of a graph G is a dominating set that locates all the vertices of G. The location-domination number of G is the minimum cardinality of a locating-dominating set in G. In this paper, we introduce and study the locating-dominating value and the location-domination polynomial of graphs and find location-domination polynomials of some families of graphs.